Radiation Pneumonitis Following Thoracic Radiotherapy: A Systematic Review - Lionel Sirait (Indonesian Journal Publisher, 2026)
Radiation pneumonitis (RP) is a clinically significant and dose-limiting complication of thoracic radiotherapy, occurring despite modern delivery techniques. Its incidence and severity are influenced by a complex interplay of dosimetric, clinical, and patient-related factors, particularly in those receiving combined-modality therapies or with pre-existing pulmonary disease.Aim: To systematically summarize the incidence, risk factors, and predictive strategies for RP in patients undergoing thoracic radiotherapy, with emphasis on clinical, dosimetric, and emerging biological predictors. A PRISMA-guided literature search of PubMed/MEDLINE was conducted from inception to January 2026 using MeSH terms related to radiation pneumonitis and thoracic radiotherapy. Original research studies involving adult patients treated with thoracic radiotherapy and reporting RP-related outcomes were included. Owing to substantial heterogeneity across studies, findings were qualitatively synthesized rather than pooled quantitatively. Twelve studies comprising approximately 1,298 patients were included. All studies demonstrated a strong association between lung dose-volume parameters and RP development. Maintaining lung V20 at approximately 20–23% was associated with lower symptomatic RP, with grade ≥2 incidence ranging from 5.5% to 13.3%. Patients with interstitial lung disease or idiopathic pulmonary fibrosis exhibited substantially higher risk, with RP ≥2 reported in up to 33% and severe RP in up to 42.1%. Emerging predictive models incorporating radiomics and biomarkers achieved AUC values up to 0.87. Lung dose exposure remains a key determinant of RP following thoracic radiotherapy. Limiting V20 to 20–23% may reduce toxicity, but individualized dose optimization, careful patient selection, and advanced risk stratification are essential — particularly in patients with underlying pulmonary disease or those receiving concurrent systemic therapies.